PENGARUH COATING KITOSAN DENGAN PENAMBAHAN ANTIOKSIDAN ALAMI TERHADAP KUALITAS FISIK DAN MIKROBIOLOGI FILLET IKAN: KAJIAN PUSTAKA - Sarah Smith; Hermawan Seftiono (Jurnal Teknologi, 2022)
The effect of chitosan coating incorporated with natural antioxidants on the quality of fish fillets stored in refrigerated storage (4 °C) for 16 days was studied and compared. The control samples (without any coating), chitosan coating, and chitosan coating incorporated with several natural antioxidants based on studies were analyzed by physical and microbiological qualities. Gallic acid (3%), rosmarinic acid (0.3%), and 6-gingerol (2%) could effectively retard physical deterioration and microorganism activity based on 25 studies. Compared to the control and chitosan coating, samples treated with chitosan and gallic acid (3%) coatings significantly maintain physical and microbial quality of fish fillets during storage.